The conservation status of the freshwater and terrestrial turtles of Mexico: a critical review of biodiversity conservation strategies - Rodrigo Macip Ríos; Rebeca Ontiveros; Saúl López-Alcaide; Gustavo Casas-Andreu (Revista Mexicana de Biodiversidad)
The continental turtle fauna of Mexico is composed of seven families, 13 genera, and 45 species; when subspecies are included, a total of 61 distinct taxa are recognized. We searched for the imperiled level or protection status of each taxon according to the IUCN Red List, CITES appendices, the 25 most endangered freshwater turtles and tortoises, and the protection lists issued by the Mexican Government. We explored the overlap of conservation status between Mexican and international agencies by comparing listing status. Among the 61 taxa, 37 were in the IUCN Red List; 16 taxa were listed on CITES appendices; 39 taxa were NOM-059; four taxa were in CONABIO’s list; and only one species was included in the world’s 25 most endangered freshwater turtles and tortoises. The Central American river turtle (Dermatemys mawii), the desert tortoises (Gopherus spp.) and the black soft shell turtle (Apalone atra) were the only taxa included in all the lists surveyed. Our comparison of the lists indicates that at least 25 taxa of Mexican turtles are lacking basic information and require further study to inform their comprehensive conservation status. Further, we detected a noteworthy discrepancy between international and Mexican conservation priorities for turtle conservation.